Android-based Stunting Child Nutrition Application (GiAS) to Assess Macro-nutrients, Zinc, and Calcium in Stunting and Non-stunting Under Two Children - Fajarini Putri Hidayat; Ma'mun Sutisna; Roni Rowawi; Hidayat Wijayanegara; Herry Garna; Atie Rachmiatie (Global Medical & Health Communication (GMHC), 2021)
Stunted children will have normal cognitive ability if nutrition is improved. The rapid brain growth in the first 1,000 days of life means that children should not be malnourished. Stunting is generally caused by a lack of macronutrients (carbohydrates, protein, and fat) and micronutrients (calcium and zinc). The mobile application called stunting child nutrition (GiAS) has features that can detect stunting, monitor toddler growth, recommend daily menus for toddlers, nutritional adequacy rate (RDA) in 2019, and others. The purpose of this study was to make it easier to distinguish macronutrients, zinc, and calcium from stunting and non-stunting children aged 12–24 months using the GiAS android application. It is conducted at the Citeureup Community Health Center, Cimahi city, for June–July 2020. The sampling technique was a simple random sampling of 88 respondents. This type of research is an observational analytic with a statistical test is a cross-sectional design. The results of the study using the Mann-Whitney test showed differences in carbohydrates (84.99±26.31 vs 151.16±68.43, p=0.001), protein (30.81±11.03 vs 60.55±38.43, p=0.001), fat (32.80±15.39 vs 64.84±47.81, p=0.001), and calcium (0.55±0.40 vs 1.43±1.16, p=0.001) and there is similarity of zinc (0.005±0.004 vs 0.010±0.016, p=0.084) after 7 days of using the GiAS application between stunting and non-stunting children. The probability value <0.05 means that the application can compare macronutrients, zinc, and calcium between stunted and non-stunted children on the 7th day. Chi-square analysis showed an increase in children's weight and height under five at two weeks and one month (p=0.001). In conclusion, the comparison of macronutrients, zinc, calcium in stunting and non-stunting children aged 12–24 months can be differentiated using the GiAS application. APLIKASI GIZI ANAK STUNTING (GIAS) BERBASIS ANDROID UNTUK MENILAI ZAT GIZI MAKRO, ZINC, DAN KALSIUM PADA ANAK STUNTING DAN NON-STUNTINGAnak stunting akan memiliki kognitif yang normal jika dilakukan perbaikan gizi yang optimal. Pertumbuhan otak yang pesat di 1.000 hari pertama kehidupan menjadikan anak tidak boleh kekurangan nutrisi. Stunting umumnya kekurangan zat gizi makro (karbohidrat, protein, dan lemak) serta zat gizi mikro (kalsium dan zinc). Aplikasi mobile bernama gizi anak stunting (GiAS) memiliki fitur yang dapat mendeteksi stunting, memantau pertumbuhan balita, merekomendasikan menu harian untuk balita, angka kecukupan gizi (AKG) tahun 2019, dan lainnya. Tujuan penelitian ini adalah kemudahan membedakan zat gizi makro, zinc, dan kalsium anak stunting dengan non-stunting usia 12–24 bulan menggunakan aplikasi android GiAS di Puskesmas Citeureup Kota Cimahi periode Juni–Juli 2020. Teknik pengambilan sampel adalah simpel random sampling sebanyak 88 responden. Jenis penelitian ini adalah analitik observasional dengan uji statistik adalah desain cross-sectional (α=0,05). Hasil penelitian  menggunakan Uji Mann-Whitney terdapat perbedaan karbohidrat (84,99±26,31 vs 151,16±68,43; p=0,001), protein (30,81±11,03 vs 60,55±38,43; p=0,001), lemak (32,80±15,39 vs 64,84±47,81; p=0,001), dan kalsium (0,55±0,40 vs 1,43±1,16; p=0,001) serta ada persamaan zinc (0,005±0,004 vs 0,010±0,016; p=0,084) sesudah 7 hari penggunaan aplikasi GiAS antara anak stunting dan non-stunting. Nilai probabilitas <0,05 berarti aplikasi dapat membandingkan zat gizi makro, zinc, dan kalsium antara anak stunting dan non-stunting pada hari ke-7. Analisis chi-square terlihat peningkatan berat badan dan tinggi badan balita pada 2 minggu dan 1 bulan (p=0,001). Simpulan, komparasi zat gizi makro, zinc, kalsium anak stunting dan non-stunting usia 12–24 bulan dapat dibedakan menggunakan aplikasi GiAS.